2019
DOI: 10.5551/jat.47597
|View full text |Cite
|
Sign up to set email alerts
|

Association between Prescription and Control Status of Dyslipidemia and Hypertension among Japanese Patients with Diabetes

Abstract: Aims: The proper management of atherosclerotic risk factors (ARFs) and attainment of target levels (TLs) for ARFs are crucial in preventing atherosclerotic cardiovascular disease (ASCVD). In this study, utilizing data from the “Specific Health Check and Guidance in Japan,” which was conducted from 2008 to 2011, we examined TL attainment status of low-density lipoprotein cholesterol (LDL-C) and blood pressure (BP) and prescription status of dyslipidemia and hypertension in patients with diabetes undergoing medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…We previously reported that SBP was the most important modi able risk factor for subsequent CVD regardless of glucose abnormality [19]. Blood pressure targets were shown to be more di cult to achieve than cholesterol targets in diabetic patients [23,24]. While a meta-analysis showed that the optimal SBP for stroke prevention was < 130 mmHg [25], the mean baseline SBP was 132 mmHg in the CAD-/CVD+/DM group in our study, which did not reach the target level.…”
Section: Onset Of Subsequent Cvdmentioning
confidence: 99%
“…We previously reported that SBP was the most important modi able risk factor for subsequent CVD regardless of glucose abnormality [19]. Blood pressure targets were shown to be more di cult to achieve than cholesterol targets in diabetic patients [23,24]. While a meta-analysis showed that the optimal SBP for stroke prevention was < 130 mmHg [25], the mean baseline SBP was 132 mmHg in the CAD-/CVD+/DM group in our study, which did not reach the target level.…”
Section: Onset Of Subsequent Cvdmentioning
confidence: 99%